Digital Everyday Maker: Praktik Governance dalam Ruang Digital - Muhammad, Ja'far; Sobari, Wawan; Pohan, Ibnu Asqori (Universitas Brawijaya, 2023)
The appearance of Dr. Tirta's participation in tackling the Covid-19 pandemic went viral on social media. This study positions Dr. Tirta as an everyday maker in governance. The aim of this research is to fill the research gap in everyday maker studies, namely exploring everyday makers in a digital context. This research uses an online-based case study method that collects data from online sources. The data analysis technique consists of three stages, namely observation, combining and grouping. This study succeeded in looking at the everyday maker in the digital world, namely the form of work in the digital world and the transformation of the everyday maker concept in the digital space as follows; First, do it yourself reinforcement. Everyday makers no longer need a large number of members to create a movement because they are assisted by the digital context of the virtual world. Second, local coverage from conventional everyday makers who face local problems can now reach things that everyday makers could not reach before. Further discussion is needed regarding the effectiveness of social media for everyday makers, in other words, regardless of the influencer's identity, they do not have social capital.